An Examination of Faceted Searching in Discovery Systems and the Impact on Information Discovery - Lai, Katie (CAML Review / Revue de l'ACBM, 2024)
This study compares the performances of the resource type facets and format facets in Primo and WorldCat Discovery respectively. Through looking at librarians’ perceived understanding of selected facets, the information retrieval mechanisms employed, and the search results yielded, the author reveals gaps between users’ perception and the information actually retrieved. The goals are to see how successful Primo and WorldCat Discovery are in making themselves a one-stop shop for music information, and to determine whether the resource type or format facets in these tools facilitate information discovery. The findings also prompt librarians to reflect on what can be done to enhance information discovery through the teaching of information literacy and through collaboration with information and systems providers.